The Digital Civility Transition Practices by Academic Community During COVID-19 Pandemic - Romeyn Perdana Putra; Egabetha Amirah Yudhaputri; Eviana Rosida; Diah Arli (Jurnal Audiens, 2023)
The digital revolution, huge changes, and digital disruption, amplified by the Covid-19 pandemic, prompted digital natives and digital immigrants to implement distance learning. Some institutions develop new learning management systems to support online learning, and also monitor academic activities such as student college attendance, posting examination case studies, and integrating exam results into student information systems. In contrast, all university members (lecturers, student college, and course management corporate) still have obstacles to using this student information system. The system implementation is unfamiliar for most members at first. Furthermore, this research is used as a qualitative method through a forum group discussion involving lecturers and student colleges of six (6) cities in Indonesia. While it is taking place in an online class, the potential risks of being exposed to electronic influences are getting more delicate. Keywords: digital civility, distance learning ethics, risks of being exposed to online impacts, online campus